“UJI EFEKTIVITAS FORMULASI EKSTRAK ETANOL BUAH PARE (Momordica charantia L.) DENGAN DAUN PEPAYA (Carica Papaya L.) SEBAGAI LOTION AEDES AEGYPTI” - SEMBIRING, TIO RANTI SARI; Simorangkir, Delisma Marsauli (Jurnal Penelitian Farmasi Dan Herbal, 2025)
Flaviviridae, genus Flavivirus, and group of arthropod-borne viruses. Aedes mosquitoes, particularly Aedes aegypti or Aedes albopictus, are the primary vectors of dengue disease transmission. A product that is used in skin-protection cosmetics to protect the skin from mosquito bites is anti-mosquito lotion (repellent). Water, emulsifying agents, humectants, and fatty ingredients make up lotion preparations. The bitter gourd and papaya leaves employed in this study were the active ingredients used to make lotion preparations. The lotion formulation used in this investigation contained flavonoid chemicals at varied extract concentrations of 0%, 2%, 4%, and 6%. The bitter gourd's and leaves' active components Because papaya is known to contain a lot of antioxidants, it can be used as an insecticide and lotion to ward against mosquitoes. According to SNI-16-4399-1996, preparations for anti-mosquito lotion made from papaya leaves and bitter melon extract pass the physical quality test because they are all homogeneous, have an oil-in-water emulsion type, are stable during storage for two weeks, and do not irritate the skin. Anti-mosquito lotion made with bitter melon fruit extract and papaya leaves, which is distinguished by the presence of dead mosquitoes in each formulation, has an effect on the effectiveness as an insecticide or repellent against mosquitoes on the skin that is applied. The extract lotion preparations' concentration The most powerful insecticide or mosquito repellant is a 6% extract of bitter gourd fruit and papaya leaves.